2014
DOI: 10.1007/s00345-014-1261-1
|View full text |Cite
|
Sign up to set email alerts
|

Both the middle and distal sections of the urethra may be regarded as optimal targets for ‘outside-in’ transobturator tape placement

Abstract: PurposeTo investigate whether the position of the tape under the urethra may influence ‘outside-in’ transobturator sling (TOT) outcome.MethodsThe study comprised 141 women who underwent TOT for clinically and urodynamically proved stress urinary incontinence. The postoperative ultrasound examination with an endovaginal biplane probe was performed before discharging the patients from hospital. The measurements obtained described the position of the tape relative to the urethra and pubic symphysis, as well as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Although abnormalities observed can be associated with urinary incontinence, such imaging is not predictive or diagnostic of the cause of the incontinence 87,88 . Ultrasonography might have a role in confirming the findings of the patient history and clinical examination, assessing postoperative complications 89 or as a means of providing biofeedback to help women to identify effective pelvic floor contraction during pelvic floor muscle training (PFMT) 90 .…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…Although abnormalities observed can be associated with urinary incontinence, such imaging is not predictive or diagnostic of the cause of the incontinence 87,88 . Ultrasonography might have a role in confirming the findings of the patient history and clinical examination, assessing postoperative complications 89 or as a means of providing biofeedback to help women to identify effective pelvic floor contraction during pelvic floor muscle training (PFMT) 90 .…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…There is a growing body of evidence that the position of the tape relative to the urethra is one of the most important factors determining sling outcome. Several studies have shown that optimally the tape should be placed between 50 and 75% of the urethral length, measured from the bladder neck to the external urethral meatus [4952] (Figs. 2 and 6).…”
Section: Ultrasound In Management Of Treatment Failure and Complicationsmentioning
confidence: 99%
“…The worst results are obtained when a tape is placed under the proximal urethra, with the failure rate exceeding 50% [52, 54] (Fig. 7).…”
Section: Ultrasound In Management Of Treatment Failure and Complicationsmentioning
confidence: 99%
“…Recurrent SUI (RSUI) is defined as a failure of anti-incontinence surgery after a period of time or persistence of SUI after a procedure aimed at correcting it. Moreover, the complication of particular concern after primary or secondary sling is the incidence of voiding dysfunction resulting usually from improper tape positioning or its excessive tension [ 9 , 10 ]. One has to remember that repeating procedures performed on vaginal skin could cause scarred vagina syndrome.…”
Section: Introductionmentioning
confidence: 99%